Optimization of Organisational Performance among Malaysian Manufacturing SMEs in Digital Age via Talent Farming - Palanisamy, Shanmuganathan; Chelliah, Shankar; Muthuveloo, Rajendran (Journal of Entrepreneurship, Business and Economics, 2021)
The purpose of the study is to enhance organizational performance among the SMEs in Malaysia in the digital age, particularly the manufacturing sector, which has an important contribution to the Malaysian economy. This study attempts to provide empirical evidence on the relationship between the four dimensions of talent farming and organizational performance in response to previous scholars' call on the influence of talent on SMEs' organizational performance. The dimensions considered in the study are talent harnessing, talent acquisition, talent retention and talent displacement. A total of 157 responses from a cross-sectional survey from Malaysian manufacturing SMEs were investigated using SPSS software version 24 and Partial Least Squares-Structural Equation Modeling (PLS-SEM). The ﬁndings reveal that talent retention and talent displacement has signiﬁcant influence organizational performance, but talent harnessing and talent acquisition have no influence on organizational performance. This research highlights the importance of talent retention and talent displacement by SME owners or leaders compared to investing on internal talent harnessing and acquiring external talent to embrace and develop their skills as a crucial step towards achieving sustainable performance for their companies. The paper provides strategic insights, practical knowledge and policies that assist SMEs in the manufacturing sector to strategies to explore another alternative approach to prepare well for the digital competencies workforce in the digital age. The novelty of this study to assist SMEs in the manufacturing sector to understand better talent farming and its important approach in formulating effective human capital strategy. The dimension of Talent Farming and conceptual research framework was chosen and formulated based on I-TOP Strategic Agility Model and Dynamic Capability Theory, respectively. The empirical analysis and the tentative conceptual framework make an important contribution towards a demand-led policy framework in the area of digital talent competencies to support for Manufacturing SMEs to overcome the talent shortage in Malaysia. The contribution and limitations of the research are discussed, and recommendations for future research are also presented. Research paper Keywords: Talent Farming; I-TOP Strategic Agility Model; Digital Age; Small Medium Enterprises (SME); Organisational Performance Reference to this paper should be made as follows: Palanisamy, S., Chelliah, S., & Muthuveloo, R. (2021). Optimization of Organisational Performance among Malaysian Manufacturing SMEs in Digital Age via Talent Farming. Journal of Entrepreneurship, Business and Economics , 9 (1), 82–120.